A Study on Factors Influencing Chinese University Students’ Intentions to Study Abroad in South-East Asia Based on Cognitive Behavioural Theory - LinPeng, Xiang; Karim, Rosman Bin (Journal of Cultural Analysis and Social Change, 2026)
Against the backdrop of advancing globalisation and the deepening Belt and Road Initiative, the South-East Asia region has emerged as a favoured destination for Chinese university students seeking study tours, owing to its unique geographical advantages and high educational value for money. Malaysia, with its rich cultural resources and relatively low cost of studying abroad, has attracted a large number of Chinese students to pursue their studies there. Beneath the rising trend of students expressing an intention to study abroad, the issues exposed in their decision-making processes have become increasingly prominent. Blind conformity, cognitive biases, and tendencies towards irrational consumption are growing more severe. Many students are easily swayed by fragmented information on social media or peer pressure without first conducting an objective assessment of the quality of education in different areas. This study, adopting a psychological cognitive perspective, identifies and guides university students' rational intention to study abroad, presenting itself as a subject requiring urgent and in-depth research within the internationalisation process of higher education. This study, grounded in the Cognitive Behavioural Theory (CBT) framework, examines the factors influencing Chinese university students' intention to study abroad in South-East Asia and the mechanisms underlying this intention. The study employed a combined qualitative and quantitative methodology, utilising questionnaire surveys and in-depth interviews to meticulously analyse the cognitive logic underlying students' study tour consumption decisions. Findings reveal that Social Thoughts, Cognitions, Self-Emotions, Feelings, and Family Behaviors/actions exert a significant positive influence on Consumption Propensity. Social Thoughts, Cognitions, and Self-Emotions, as well as Feelings, also exert a significant positive influence on Personal Initiative. Family Behaviours Actions did not demonstrate a significant impact on Personal Initiative. Personal Initiative exhibits a mediating effect between Social Thoughts and Cognitions, Self-Emotions and Feelings, Family Behaviours and Actions, and Consumption Propensity. This study proposes that international exchange departments within higher education institutions should enhance students' information screening capabilities through advisory services. It actively advocates for the establishment of a supportive network comprising professional university guidance, rational family decision-making, and standardised social information provision. This approach aims to reduce blind consumption arising from information asymmetry, thereby promoting the healthy and sustainable development of the study tour market.